Persepsi dan tingkat partisipasi masyarakat Suku Yali dalam pemanfaatan hutan tradisional di Distrik Abenaho Kabupaten Yalimo - Mabel, Elifas; Moeljono, Soetjipto; Ungirwalu, Antoni (Cassowary, 2025)
ABSTRACT: Over the last four decades, large-scale forest management in Papua has failed to deliver wealth for most Papuans, and even the minus reveals that Papuans are the poorest in Indonesia. Environmental sustainability is improving, and increased community participation in teak forest management will impact the economy (community income increases) and the ecology. Forest management is linked to local knowledge or how humans see and act due to their interpretation of the natural environment, which is interwoven into the cultural system. This study used a descriptive qualitative research approach from January to February 2022 in Abenaho District, Yalimo Regency. The findings of a study on the usage of traditional woods by the Yali tribal population in Abenaho District reveal two distinct characteristics of the area, which may be seen in the management and utilisation activities of these traditional forests. Traditional forest utilisation systems such as farming/gardening, use of forest products, flora and fauna are also found to differ between the villages of Uwambo, Yahatma, Elesim Amuki, Kefido and Horenikma, Usabie, Kelesu, Kaboholik, and Suele.